The Association Between Peer Influence and Dating Behavior Among Adolescents at a High School in Rural Area: A Cross-Sectional Study - Amalia, Ananda Putri; Silvanasari, Irwina Angelia (Al-Hijrah Indonesia, 2025)
Background: Dating behavior among adolescents today leads to risky dating behavior that has an impact on premarital sexual behavior. Teenagers are curious about new things and can be influenced by their partners, environment, and peers. Purpose: This study aims to analyze the relationship between the role of peers and dating behavior in adolescents. Methods: This research design is quantitative with a cross-sectional approach. The population at State Senior High School